The Effective Way of Cultivating the Mind Based on Wise Attention (Yoniso-manasikāra) - Anh Thi, Bhikkhuni Do Le; Dhammahaso, Phramaha Hansa; Piyabhani, Phramaha Nantakorn (Journal of International Buddhist Studies, 2022)
Wise attention is an important condition on the journey to true happiness. When the mind is developed, life becomes brightener happier. Zen master Thich Nhat Hanh argues that “The way out is in” meaning that your behavior depends on how you nourish your mind, depend on the way to creating a path of thought. Abhidhamma called the thought process, the cognitive process, the process of the mind. Wise Attention (Yoniso-manasikāra) is a vital factor for living one’s life correctly, a life lived in such a manner is considered a virtuous life. This article focuses on an effective method for Mind Cultivation based on Yoniso-manasikāra (MCBY) process. If the practitioners follow the MCBY process, they will be transformed their bad behavior, bad speech, and negative thinking. They know how to live mindfully in every moment, creating their lives happier and happier.